Analysis of Junior High School Students' Scientific Literacy Skills in Supporting the Achievement of Sustainable Development Goals (SDGs) - Novita Trisanti; Yuni Sri Rahayu; Titin Sunarti (Postgraduate, University of Mataram, 2025)
This research is meant to analyze students' scientific literacy skills. Scientific literacy is one of the key skills needed to develop a generation capable of solving problems and overcoming challenges, which will support the achievement of the Sustainable Development Goals (SDGs). This research is descriptive research using a mixed method, and uses data collection techniques in the form of scientific literacy tests and interviews with science teachers. The competencies used as a reference for analysis are the scientific literacy competencies developed by PISA, namely: the first competency is explaining phenomena scientifically; the second competency is constructing and evaluating designs for scientific investigations and critically interpreting scientific data and evidence; and the third competency is researching, evaluating, and using scientific information for decision-making and action The results of a research study conducted at a public junior high school in the Bangkalan area, involving 68 students, showed that the students' scientific literacy skills were still in the low category, with many influencing factors, both external and internal to the students. The conclusion of this study is that low science literacy skills pose a challenge to supporting the SDGs. Therefore, a transformation in science learning processes is needed to train students' scientific literacy skills to support the achievement of several SDGs.